2019
DOI: 10.1108/bij-10-2018-0337
|View full text |Cite
|
Sign up to set email alerts
|

Lean readiness within emergency departments: a conceptual framework

Abstract: Benchmarking: an International Journal Lean readiness within emergency departments: A conceptual framework AbstractPurpose -The purpose of this study was to develop a framework to assess the lean readiness within emergency departments (EDs) and identify the key quality practices deemed essential for lean system (LS) implementation. Methodology-An extensive review of lean healthcare literature was conducted, including LS implementation within the healthcare sector (both generally and in EDs), best ED quality pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 73 publications
(178 reference statements)
0
51
0
1
Order By: Relevance
“…Many works of literature have suggested that lean is implemented and assessed in different service sectors. For example, Alnajem et al ( 2019 ), Hussain and Malik ( 2016 ), Agarwal et al ( 2016 ), and Robinson et al ( 2012 ) have implemented this study in different parts of a hospital such as emergency, cardiac catheterization laboratory, etc. Narayanamurthy et al ( 2017 ) and Thomas et al ( 2017 ) have implemented this in the higher educational institute sector to improve the course plan and to reduce absenteeism in class.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many works of literature have suggested that lean is implemented and assessed in different service sectors. For example, Alnajem et al ( 2019 ), Hussain and Malik ( 2016 ), Agarwal et al ( 2016 ), and Robinson et al ( 2012 ) have implemented this study in different parts of a hospital such as emergency, cardiac catheterization laboratory, etc. Narayanamurthy et al ( 2017 ) and Thomas et al ( 2017 ) have implemented this in the higher educational institute sector to improve the course plan and to reduce absenteeism in class.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The psychosocial work climate refers to a positive commitment of all staff and is negative when neglected, mainly due to its leadership. In the same vein, Alnajem et al [ 41 ] highlight the influence of senior management on encouraging positive relations between health professionals, patients, and suppliers. Multisdisciplinary reinforces improvement in Teamwork and standardization of activities.…”
Section: Research Problems Approaches and Applied Toolsmentioning
confidence: 99%
“…The following section explains the three phases of LSS implementation and sustainability roadmap for reducing medication errors. These three phases were developed based on the existing literature including Kumar et al (2011), Al-Balushi et al (2014, Antony et al (2016), Timans et al (2016), and Alnajem et al (2019).…”
Section: Lss Implementation and Sustainability Roadmap To Reduce Medication Errorsmentioning
confidence: 99%
“… Effective communication between healthcare practitioners and departments is crucial (Alnajem et al, 2019).  Effective communication entails top-down and bottom-up communication (Antony and Banuelas, 2002).…”
Section: Effective Communication At All Levelsmentioning
confidence: 99%